STANDAR PELAYANAN PUBLIK DALAM PENGURUSAN KARTU KELUARGA DAN KARTU TANDA PENDUDUK PADA KANTOR PEMERINTAHAN KECAMATAN COLOMADU - Afandi, Moh Yusuf; Suwardi; Sugiyarti, Sri Riris (Solidaritas, 2024)
This research is "Public Service Standards in Arranging Family Cards andResident Identity Cards at Colomadu District Government Offices". InColomadu District there is a need to improve services because there are stillproblems with delays in making and publishing population administrationdocuments because the SOP has not been implemented optimally. Public Service Standards in Managing Family Cards and Resident IdentityCards at the Colomadu District government office were analyzed using thepublic administration service quality theory from Zeithaml, Berry andParasuraman in Fandy Tjiptono, (2005:70), there are 5 indicators, namelytangible dimensions, reliability dimensions, responsiveness , service qualityassurance, care. The results of this research can be concluded that public servicestandards in making KK and KTP at the Colomadu District government officeare good, such as having service support facilities, clear service procedures,employee ability to use tools during the service process, employee ability toprovide information to the public, respond every service user who wants to getservices, provides cost guarantees and guarantees of certainty in KK and KTPservices, Colomadu District public services have implemented care and put theinterests of service users first, employees serve with courtesy and non-discrimination, employees also accept suggestions and criticism from the publi